Controlling pitch length of chiral monomer-doped nematic/cholesteric liquid crystals using photopolymerization - Liu, Cheng-Kai; Fuh, Andy Ying-Guey; Chen, Yuan-Di; Cheng, Ko-Ting (Journal of physics. D, Applied physics, 2010)
This work presents a simple approach to control the pitch length of chiral monomer-doped nematic/cholesteric liquid crystals (CM-NLCs/CM-CLCs) using photopolymerization. Illuminating CM-NLCs/CM-CLCs with unpolarized UV light causes the diffusion and polymerization of CM, and then increases/decreases the pitch length by reducing the concentration of the CM in the bulk. It should be noted that the pitch length change is irreversible in either red- or blue-shift. The key to control the pitch length of CM-NLCs/CM-CLCs is the competition between the right- and left-hand chiral dopants in the sample. CM-NLCs and CM-CLCs are used to study the red- and blue-shifts, respectively. The properties of cobweb-like polymer layers are also discussed.